Comparing the solar minima of cycles 22/23 and 23/24: The view from LASCO white light coronal images. Issue 1 (21st January 2014) - Lamy, P.; Barlyaeva, T.; Llebaria, A.; Floyd, O.
<x xml:space="preserve">Abstract</x> The Large Angle and Spectrometric Coronagraph LASCO‐C2 aboard SOHO has now completed 17 years (1996–2012) of quasi‐continuous white‐light imaging of the corona from 2.2 to 6.5 solar radii, thus allowing an unprecedented view of its evolution over a solar cycle and a half including the minima of solar cycles 22/23 and 23/24. The corrected and calibrated polarization sequences produce images of the radiance (B), the polarized radiance (pB), and the electron density Ne of the K corona, and, in turn, of their synoptic maps. Their temporal variations are quantified by integration first globally, then in the north and south hemispheres, and finally, in sectors of 30° latitudinal extent centered along the equatorial and polar directions. The global radiance of the K corona follows well the solar activity as described by the sunspot number and the radio flux and was 24% fainter during the minimum of solar cycle 23/24 than during that of cycle 22/23. However, the two hemispheres experienced different reductions, 17% for the north one and 29% for the south one. The equatorial sector suffered a drastic reduction of 44%, in remarkable agreement with the in situ measurements of Wind and ACE at 1 AU, whereas the north and south polar sectors did not experience much variation. Cycle 23 is estimated to have lasted 12 years and 3 months. Maximum conditions have been reached in the northern region, whereas the southern region is still lagging. Finally, the rate of coronal mass ejections follows well the solar activity.